Electrospinning of botanicals for skin wound healing - Guo, Shijie; Wang, Pengyu; Song, Ping; Li, Ning (Frontiers in Bioengineering and Biotechnology, 2022)
Being the first barrier between the human body and external environments, our skin is highly vulnerable to injuries. As one of the conventional therapies, botanicals prepared in different topical formulations have been applied as medical care for centuries. With the current increase of clinical requirements, applications of botanicals have been headed toward nanotechnologies, typically fused with electrospinning (ES) that forms nanofibrous membranes suitable for skin wound healing. In this review, we first introduced the main process of wound healing, and then presented botanicals integrated into ES membranes as either loaded drugs, or carriers, or membrane coatings. In addition, by addressing functional features of individual botanicals in the healing of injured skin, we further discussed the bioactivity of ES membranes with botanicals in relevant to the medical issues solved in the process of wound healing. As achieved by pioneer studies, due to infrequent adverse effects and the diversity in resources of natural plants, the development of ES products based on botanicals is gaining greater attention. However, investigations in this field have mainly focused on different methodologies used in the preparation of botanical nanofiber membranes, their translation into clinical practices remains unaddressed. Accordingly, we propose that potential clinical applications of ES membrane containing botanicals require further expansion of the arsenal for bioactive components, the clarification of their molecular actions, the establishment of standard criteria for evaluations of wound healing, and updated technologies for a large-scale production.